Effect of welding parameters on diffusion bonding of type 304 stainless steel-copper bimetal - Yilmaz, O (I O M Communications Ltd Inst Materials, 2001)
Stainless steel AISI type 304 and electrolytic cold rolled copper were joined by diffusion bonding at temperatures ranging from 650 to 950 degreesC, for times from 5 to 45 min, and at pressures from 2 to 12 MPa. After bonding the microstructure of the interface was investigated, including the grain size, and shear and tensile strengths of the bonded specimens were determined. From the results, it was seen that the bond shear strength was dependent on interface grain boundary migration and on grain growth during the bonding process. In addition, attempts were made to find a relationship between grain size and shear strength in the bonding area. Taking into account the results of shear testing and microstructural observation, for a sound bond, optimum bonding conditions were obtained at temperatures of 800-850 degreesC for 15-20 min at 4-6.5 MPa. The fracture behaviour of the diffusion bonded joint was investigated by means of shear and tensile testing under different bonding conditions. It was found that both shear and tensile strengths of the bonds were sensitive to the bonding conditions, and the intermetallic phases did not affect these parameters. Furthermore, the value of shear strength of the bond surface determined by shear testing was higher than the shear strength of the fracture surface determined by tensile testing. (C) 2001 IoM Communications Ltd.